IMPLEMENTATION OF PUBLIC PARTICIPATION IN THE MAKING OF REGIONAL REGULATIONS IN NORTH KOLAKA REGENCY ACCORDING TO ACT OF THE REPUBLIC OF INDONESIA NO. 12/2011 CONCERNING THE MAKING OF LEGISLATION - Andi Akbar Herman Andi Akbar Herman (Al-Syakhsiyyah: Journal of Law & Family Studies, 2021)
The making of legislation has recently become a subject of discussion among communities, such as the very low level of community participation, arbitrary actions in the making of laws and regulations, the establishment of legislation that seems to be a rushed law product, the Covid-19 pandemic that restrict people to have a gathering to capture the community aspirations, and the establishment of all forms of regulations under the act that may affect people’s mobility in social life.The present study aims to find out the roots of problem concerning the extent of public participation in the making of regional regulations in North Kolaka Regency, Kendari, Indonesia.  Therefore, it is expected that the legislation will be issued in accordance with the will of community and the Act of the Republic of Indonesia No. 12/2011 concerning the Making of Legislation, as amended by the Act of the Republic of Indonesia No. 15/2011 concerning Amendments to the Act of the Republic of Indonesia No. 12/2011 concerning the Making of Legislation.The author employed the combination of normative legal research and empirical legal research as the type of this study. The results indicated that the regional regulations that have been ratified will not be well applicable and effective at the implementation level, since they are not in accordance with the instructions for the making of regional regulations as regulated in the legislation. The presence of regional regulations that do not accommodate all the public interests as well as the low level of public participation will then create a new problem among community. For this reason, more comprehensive public involvement is needed, whether in the form of public sharing, FGD (Focus Group Discussion), or the help of experts in Bapemperda and Regional Government who specifically handle the issue on the making of regional regulations. Keywords: Participation, Public, Regional Regulations